Pelatihan Penggolahan Sampah Organik Skala Rumah Tangga Menggunakan Metode Keranjang Takakura - Neri Puspita Sari; Benriwati Maharmi; Zaiyar; Yulia Setiani; Silfia Rini (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Every day people always produce household waste. In an average day each resident produces 2-3 liters of waste. To reduce the amount of waste that is disposed of in the TPA, the community needs to carry out their own waste processing techniques. The most appropriate method of processing organic waste is to use the compost. Compost is an effort to process organic waste through a controlled decomposition process. The main product of composting is environmental cleanliness, because the amount of disposing organic waste in the landfill that can be reduced. Subsequence, it can be obtained the compost yield as another advantage. Composting with the Takakura method is very suitable for tropical areas and household scale.